DEVELOPMENT OF BAMBOO (OXYTENANTHERA ABYSSINICA) STEM AS IRRIGATION PIPE (2010)
Modern micro irrigation materials are very effective when correctly installed and maintained but their main disadvantage in the Nigerian farming situation is their relatively high cost. This study developed bamboo (Oxytenanthera abyssinica) as irrigation pipe and determined some of its hydraulic properties namely; burst strength, head loss and friction factor with a view to determining its potentials as irrigation pipe to reduce cost and technology required. These properties were found to vary, some of them significantly, along the culm height. Its bursting pressure averages about 13 x IFN/m2, which is low compared to about 23.1 xlF N/rrf for aluminum pipe but higher than 11.2 x IF N/m2 for PVC pipe currently in use as irrigation and drainage pipes. The mean friction factor, f, determined within the turbulent (Net 20001 range in a 6 m length, 2.6 mm internal diameter bamboo pipe discharging at about 5.3 x 104 rri3/s was 0.020 giving a mean head loss of 0.14 mJm. Biodegradabihty, haulage and high friction factor due mainly to pipe roughness have been identified as problem areas requiring future studies.